Remote detection of hyperpolarized (129)Xe resonances via multiple distant dipolar field interactions with (1)H - Zhang, Le (J Chem Phys, 2016)
A remote detection scheme utilizing the distant dipolar field interaction between two different spin species was proposed by Granwehr et al. [J. Magn. Reson. 176(2), 125 (2005)]. In that sequence (1)H spins were detected indirectly via their dipolar field interaction with (129)Xe spins, which served as the sensing spins. Here we propose a modification of the proposed detection scheme that takes advantage of the longer T(1) relaxation time of xenon to create a long lasting dipolar field with which the fast relaxing (1)H spins are allowed to interact many times during a single acquisition. This new acquisition scheme improves detection sensitivity, but it also presents some challenges.